Linear Programming Models and Methods of Matrix Games with Payoffs of Triangular Fuzzy Numbers - Li, Deng-Feng.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book addresses two-person zero-sum finite games in which the payoffs in any situation are expressed with fuzzy numbers. The purpose of this book is to develop a suite of effective and efficient linear programming models and methods for solving matrix games with payoffs in fuzzy numbers. Divided into six chapters, it discusses the concepts of solutions of matrix games with payoffs of intervals, along with their linear programming models and methods. Furthermore, it is directly relevant to the research field of matrix games under uncertain economic management. The book offers a valuable resource for readers involved in theoretical research and practical applications from a range of different fields including game theory, operational research, management science, fuzzy mathematical programming, fuzzy mathematics, industrial engineering, business and social economics. .
Part 1 Matrix Games with Payoffs of Fuzzy Numbers -- Interval-Valued Matrix Game -- Matrix Games with Payoffs of Triangular Fuzzy Numbers -- Part 2 Constraint Matrix Games with Payoffs of Fuzzy Numbers -- Interval-Valued Constraint Matrix Games -- Constraint Matrix Games with Payoffs of Triangular Fuzzy Numbers -- Constraint Matrix Games with Payoffs of Trapezoidal Fuzzy Numbers.
Keywords: Operations research; Econometrics; Game theory; Operations Research and Decision Theory; Quantitative Economics; Game Theory